Sistema web de gestión de los servicios del área del restaurante en el Hotel Higuerón de la ESPAM MFL - López Vélez, Magdalena Jamilet (2024)
The main objective of this project was to create a web system to manage the restaurant services of Hotel Higuerón at ESPAM MFL, with the aim of automating the control of the quantities of ingredients used in the preparation of food dishes. To achieve this goal, information and system requirements were gathered through client interviews. Subsequently, the guidelines of the IEEE 830 standard were applied to specify the software requirements. The architecture selected for the system was client/server, using the Model-View-Controller (MVC) model due to its advantages and suitability for the project's requirements. The system was developed using the SCRUM methodology, following its phases of initiation, planning and estimation, implementation, review and retrospective, and release. Once developed, the system’s proper functioning was verified through exhaustive testing, and finally, it was deployed in production. The resulting system allows users to search for specific dishes and calculate the exact amount of ingredients needed based on the number of servings, thus avoiding waste. Additionally, when a dish is registered, the system automatically calculates and deducts the quantities of ingredients used, which facilitates weekly purchase planning and ensures the acquisition of adequate amounts for the entire week. This optimizes the use of ingredients without functioning as an inventory, focusing on precise calculations to prevent waste.